2019
DOI: 10.1186/s12931-019-1038-6
|View full text |Cite
|
Sign up to set email alerts
|

AGER expression and alternative splicing in bronchial biopsies of smokers and never smokers

Abstract: Cigarette smoking is one of the major risk factors for the development of chronic obstructive pulmonary disease (COPD). Evidence is accumulating that Receptor for Advanced Glycation-End products (RAGE)-signaling is a key pathway in the pathophysiology of COPD. To date, it is unknown how smoking affects RAGE expression. In the current study, we investigated the effect of smoking on AGER , the gene encoding RAGE, expression and on alternative splicing of AGER . To th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…We have previously shown that current smoking is associated with significantly lower levels of AGER bronchial gene expression in healthy subjects 34 (Figure 6A; Table 1). Thus, we extended these studies to determine whether smoking impacts TLR4 bronchial gene expression in healthy subjects and whether it impacts AGER and TLR4 gene expression in COPD patients.…”
Section: Resultsmentioning
confidence: 75%
“…We have previously shown that current smoking is associated with significantly lower levels of AGER bronchial gene expression in healthy subjects 34 (Figure 6A; Table 1). Thus, we extended these studies to determine whether smoking impacts TLR4 bronchial gene expression in healthy subjects and whether it impacts AGER and TLR4 gene expression in COPD patients.…”
Section: Resultsmentioning
confidence: 75%
“…In line with this, there is a need to investigate the therapeutic options of inhibiting either the release or activity of ECM DAMPs in fibrosis. DAMPs, have been well characterised in terms of their role in inflammaging, particularly RAGE ligands, which have a well characterised role in innate immune driven pathologies such as COPD, OA and asthma [248][249][250][251]. However, the contribution of DAMPs and the effect of targeting this therapeutically in fibrosis is less well explored.…”
Section: Targeting Senescence As a Potential Therapeutic Approach For The Treatment Of Fibrotic Diseasementioning
confidence: 99%
“…Recently, we showed that AGER expression was lower in lung tissue from smokers compared with never-smokers, and that smoking of three cigarettes severely decreased the serum levels of sRAGE within 2 h [ 4 ]. Furthermore, we showed that smokers display increased alternative splicing of AGER into the endogenous soluble splicing form [ 9 ]. Interestingly, we also showed that unlike plasma sRAGE levels, the levels in induced sputum did not correlate with COPD status [ 5 ].…”
mentioning
confidence: 99%
“…sRAGE levels were measured in serum and sputum supernatant using ELISA (Human RAGE Duoset ELISA, DY1145; R&D Systems, Minneapolis, MN, USA) according to the manufacturer's protocol. mRNA levels and splicing of AGER was measured in bronchial biopsies as described previously [ 9 ]. In short, mRNA expression analysis was performed using raw counts of AGER and analysed using the R-package DESeq2 [ 9 , 11 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation